2007
DOI: 10.1002/cd.184
|View full text |Cite
|
Sign up to set email alerts
|

Conventionality in family conversations about everyday objects

Abstract: Children' s developing understanding that words have conventional meanings and objects have conventional functions emerges in parent- Conventionality in Family Conversations About Everyday ObjectsMaureen A. Callanan, Deborah R. Siegel, Megan R. Luce Conventionality is central to theories of the development of language and thought. There is, however, some ambiguity in how conventionality is understood. Conventional meanings must be stable enough at a global level so that one can assume that others in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In particular, Callanan and colleagues have suggested that the way in which parents label objects when speaking to children (Callanan & Sabbagh, 2004) and the way in which parents demonstrate the uses of objects to children (Callanan, Siegel, & Luce, 2007) may endorse the notion that there is a best way to label and use objects. According to this proposal, conventionality would be limited to knowledge forms about which children receive this type of rich parental input.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, Callanan and colleagues have suggested that the way in which parents label objects when speaking to children (Callanan & Sabbagh, 2004) and the way in which parents demonstrate the uses of objects to children (Callanan, Siegel, & Luce, 2007) may endorse the notion that there is a best way to label and use objects. According to this proposal, conventionality would be limited to knowledge forms about which children receive this type of rich parental input.…”
Section: Discussionmentioning
confidence: 94%
“…With these parameters in mind, and inspired by sociocognitive approaches to the acquisition of culture (Callanan, Siegel, & Luce, 2007; Tomasello, Carpenter, Call, Behne, & Moll, 2005), we posit below a number of candidate cues children might use to define the domain of conventionality. These are cues about how people use certain forms—which should inform children about what is conventional—and cues about who uses these forms—which should inform children primarily who is conventional.…”
Section: Accounting For Conventionality: Challenges and Possible Solumentioning
confidence: 99%
“…A fourth and final cue has to do with pragmatic or semantic indications offered by adults (Callanan et al., 2007). For instance, Callanan and Sabbagh (2004) found that when interacting with their children, parents typically engage in labeling strategies that may convey to children that there is a best way to refer to objects (e.g., insisting on a single label for each object).…”
Section: Accounting For Conventionality: Challenges and Possible Solumentioning
confidence: 99%
See 1 more Smart Citation
“…According to one proposal, children receive cues from the input about how to treat a certain form. Specifically, the claim is that adults often indicate to children that there are preferred ways to express certain concepts or use objects (Callanan & Sabbagh, 2004;Callanan, Siegel, & Luce, 2007;. A second proposal suggests that young children's assumption of conventionality derives from their limited capacity to understand that others have a subjective representation of reality (Sabbagh & Henderson, 2007).…”
mentioning
confidence: 97%